Comparative evaluation of use of a diode laser and electrode application with and without two dentinal tubule occluding agents in the management of dentinal hypersensitivity - A clinical study - Chitra Laxmikant Patil; Dilip Ganpat Pol; Rajesh Prabhakar Gaikwad (Wolters Kluwer Medknow Publications, 2020)
Background: Dentinal hypersensitivity (DH) is common problem in dentistry. Traditional agents along with alternative therapies have been researched. Aim: To study the efficacy of a diode laser (DL) and electrode application with and without hydroxyapatite (HAP) and strontium chloride (SrCl2) powder. Materials and Methods: 60 Patients with mild cervical abrasion in at least two quadrant with two teeth per quadrant were selected and randomly divided into four groups: (i) Group 1- DL versus DL with HAP (ii) Group 2 - electrode application versus electrode application with HAP (iii) Group 3 - DL versus DL with SrCl2 (iv) Group 4 - electrode application versus electrode application with SrCl2 and were subjected to tactile stimulus and air blast test and scores were recorded on verbal rating scale (VRS) and visual analogues scale (VAS) at different time for 3 months. The data was statistically evaluated by one way ANOVA and paired t test. Results: In group 1 and 3, DL alone had a short term reduction of hypersensitivity (P = 0.001). Synergistic effect of DL and HAP (group 1) showed a prolonged reduction on both scales (P < 0.001) whereas the additive effect of SrCl2 with DL (group 3) showed statistically significant reduction on both scales at all time (p< 0.001). In group 2 there is insignificant difference on both scales at all time (P > 0.05) however group 4 showed significant reduction only in VAS score (p>0.05). Conclusion: DL alone had a short lived effect however with adjunctive sustained results were obtained whereas electrode application was neither beneficial nor did cause any adverse effect.